3-D Antenna Array Structures for Millimeter Wave Multi-User Massive MIMO Hybrid Precoder Design: A Performance Comparison - Mahmood, Mobeen; Koc, Asil; Le-Ngoc, Tho (IEEE communications letters, 2022)
In this letter, we investigate the performance of various three-dimensional (3D) array structures in the design of hybrid precoder (HP) for millimeter wave (mmWave) multi-user massive multiple-input multiple-output (MU-mMIMO) systems. The proposed HP scheme involves two stages: (i) RF beamforming based on singular value decomposition (SVD) of channel matrix, and baseband MU precoding based on the instantaneous effective baseband channel to mitigate MU-interference by a regularized zero-forcing (RZF) technique. Illustrative results show that, in comparison to two-dimensional (2D) arrays, 3D array structures can provide high spectral and energy efficiencies as well as non-varying achievable rate independent from the user angular location.